The physicochemical characterization of an aminoester-type epoxy-resin hardener prepared from chemical degradation of poly(ethylene terephthalate) - Spychaj, T.; Pilawka, R. (Polimery, 2022)
Chemical degradation of PET scrap was performed by amino-glycolysis with triethanoloamine (TEA) at 180-220°C for 90-360 min and PET/TEA mole ratio 1:2. The reaction products were separated with 2-buta-nol or isopropanol as solvent into the alcohol-soluble epiphase and the alcohol-insoluble hypophase fractions. Each fraction was evaporated for 6-9 h at 60-80°C in vacuo to remove the solvent. Viscosity, hydroxyl number, size exclusion chromatograms, FTIR and :H and 13C-NMR spectra were measured for the original PET/TEA product and for the fractions. Property differences between the products were explained in terms of side reactions of dehydration of -N(CH2CH2OH)2 groups. Rheometric curves were ascertained at room temperature to 200°C to follow the crosslinking processes in the Epidian 6 compositions containing the PET/TEA product as hardener used with the ratios 1:4-1:8 of hardener’s tertiary N to resin’s epoxy groups and of the Epidian 6 (Bisphenol A) compositions containing one PET/TEA fraction (115S or 115P) or the nonfractionated PET/TEA product as hardener (N/epoxy ratio 1:5). Heat effects accompanying the crosslinking reaction run in the above compositions were followed by DSC. The thermograms disclosed that, in terms of the reaction enthalpy, the product most reactive toward epoxy resin was the alcohol-soluble PET/TEA fraction.